Advances in Biodegradable Polymers: Synthesis, Properties and Environmental Applications - Saini, Shallu; Saini, Manuj; Tuli, Hardeep Singh; Pathania, Amit; Kaur, Damandeep; Bhatia, Gurpreet Kaur; Varshney, Deekshant; Singh, Subhav (Asian Journal of Chemistry, 2026)
Increased apprehension about the environment due to the extensive use of plastics originating from petroleum has led to the development of biodegradable polymers as prospective replacements for several industrial and environmental applications. Biodegradable polymers are important materials for the circular economy and sustainable resource management due to their degradation into environmentally benign products in a controlled manner. This review presents the current state of research on biodegradable polymers, covering their classification, sources, synthesis methods, structural characteristics, physicochemical properties and environmental applications. Biodegradable polymers derived from natural, synthetic and microbial sources are discussed with emphasis on their structural features and their influence on thermal stability, mechanical properties, degradation behaviour and processability. Recent developments in material design and processing include advances in chemical polymerization, microbial fermentation and green synthesis approaches. Their applications in sustainable food packaging, agriculture, wastewater treatment, environmental remediation and eco-friendly consumer products are also examined in relation to the growing need for alternatives to conventional plastics. Biodegradable polymers represent a promising class of sustainable materials with the potential to reduce plastic pollution, improve resource efficiency and support environmental sustainability. Continued research in polymer design, processing technologies, multidisciplinary material development and supportive regulatory frameworks is needed to facilitate their wider industrial application and realize their long-term environmental benefits.